2013
DOI: 10.1519/jpt.0b013e31827bc497
|View full text |Cite
|
Sign up to set email alerts
|

Screening Postmenopausal Women for Fall and Fracture Prevention

Abstract: Fragility fracture prevention has been historically associated with the diagnosis and treatment of osteoporosis. Given that the strongest determinant of fracture is falls, it is critical to add fall risk into clinical decision-making guidelines for fracture prevention. This special interest paper proposes an algorithm based on 2 validated tools: (1) World Health Organization's Fracture Risk Assessment Tool, which evaluates probability of fracture and (2) Functional Gait Assessment, which evaluates fall risk. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…18 Koreans frequently dine out and regularly consume liquid cuisines, such as Jjigaes, which contain salt and salt-fermented food 7 ; these eating habits may help explain, in part, why the Korean population consumes such a high salt diet. Various factors are attributed to the development of osteoporosis, including a lack of physical activity, smoking, and calcium deficiency [19][20][21] ; however, sodium intake is not widely regarded as a risk factor for osteoporosis. Although there is a steady stream of campaigns aimed at reducing salt intake to prevent and treat hypertension, 7,22 few similar campaigns have been aimed at preventing osteoporosis among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Koreans frequently dine out and regularly consume liquid cuisines, such as Jjigaes, which contain salt and salt-fermented food 7 ; these eating habits may help explain, in part, why the Korean population consumes such a high salt diet. Various factors are attributed to the development of osteoporosis, including a lack of physical activity, smoking, and calcium deficiency [19][20][21] ; however, sodium intake is not widely regarded as a risk factor for osteoporosis. Although there is a steady stream of campaigns aimed at reducing salt intake to prevent and treat hypertension, 7,22 few similar campaigns have been aimed at preventing osteoporosis among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors are attributed to the development of osteoporosis, including a lack of physical activity, smoking, and calcium deficiency 19-21 ; however, sodium intake is not widely regarded as a risk factor for osteoporosis. Although there is a steady stream of campaigns aimed at reducing salt intake to prevent and treat hypertension, 7,22 few similar campaigns have been aimed at preventing osteoporosis among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have suggested that independent risk factors for falls in postmenopausal women may be related to smoking, menopausal age, bone density, drug use and previous medical history [11,13]. However, since the published literature contains mostly single-centre cohort studies, they differ in the identification of certain risk factors (such as alcoholism and hormone use) [14][15][16], and further research is urgently needed to identify the risk factors for falls in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…9,[78][79][80] These interventions can potentially decrease fall and fracture risk and improve a client's quality of life. [79][80][81] A recent Delphi consensus on physical activity guidelines for persons with OP concluded that clients with OP should be assessed by an exercise professional for fracture risk, fall risk, posture, and physical performance parameters such as strength, pain during movement, gait speed, body mechanics, balance, flexibility, and aerobic capacity. 9 Those with OP plus known spinal fractures are recommended for physical therapy consultation and treatment for education on spinesparing techniques and supervised exercise prescription to prevent fall and fracture risk.…”
Section: Discussionmentioning
confidence: 99%